Performance study of different farm level potato storage practices in Pakistan - Iqbal, Muhammad Qasir; Ilangantileke, S.G.; Jindal, Vinod Kumar; Athapol Noomhorm; Vincent, Jean-Claude; The British Government (Bangkok : Asian Institute of Technology, 1994)
A study was conducted to investigate the performance of different on-farm potato storage systems. A red-skinned potato variety Desiree was stored for three months (March through May). Three improved systems, the naturally ventilated clamp, the forced ventilated clamp and the evaporative cooled storage structure were studied, keeping an unventilated clamp (farmer's practice) as control. The percent weight loss, percent sprouting, specific gravity, dry matter content, rotting and firmness of the stored potato were major parameters investigated in four storage systems. Sampling cells were installed in the potato heaps of all storage systems, to facilitate observation of potatoes at the top, center and bottom of the heaps, at weekly intervals. Temperature and relative humidity of ambient as well as inside the storage systems was observed regularly, throughout storage. The storage systems were also analyzed in terms of costs incurred per ton of potato storage. Net benefits and benefit cost ratios were calculated for each system, based on the market price of the stored potatoes, at regular intervals. Results indicated that, of the four storage systems, the highest weight losses (24% ), in terms of moisture loss, sprouting and rotting were in the unventilated clamp. Total weight losses for the naturally ventilated clamp, the forced ventilated clamp and the evaporative cooled store were found to be 13.3%, 10.5%, and 6%, respectively. The evaporative cooled store had the highest storage cost, but the higher market price obtained for potatoes stored in this system and lowest storage losses proved this system best of the four, in terms of net benefits.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Environment, Resources & Development
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Potatoes -- Pakistan; Fruit -- Pakistan -- Storage